Transforming Budgeting Practices in the Digital Economy: A Systematic Review of Technological Advances and Digital Literacy - Bahtiar , Muhammad Yusuf; Iswari, Hanif Rani; Fairuzabadi, Ahmad (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study aims to systematically review the transformation of budgeting practices within the digital economy, focusing on the integration of digital technologies and digital literacy. Employing the PRISMA-based Systematic Literature Review (SLR) approach, the research analyzes 156 selected articles from five major databases published between 2015 and 2024. The findings reveal that technologies such as cloud computing, artificial intelligence, and big data analytics significantly enhance the efficiency, transparency, and accountability of budgeting systems across both public and private sectors. However, the success of this transformation is highly dependent on users’ digital literacy levels. The study also identifies research gaps, particularly the lack of longitudinal studies and frameworks for digital literacy development in budgeting. These insights offer theoretical contributions to technology adoption models and provide practical implications for policymakers, financial managers, and system developers in designing adaptive and sustainable budgeting strategies in the digital era.